2008
DOI: 10.1016/j.bbadis.2008.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Parameters of oxidative stress are present in the circulation of PXE patients

Abstract: Pseudoxanthoma elasticum (PXE) is an inherited disorder characterized by calcification of elastic fibres leading to dermatological and vascular alterations associated to premature aged features and to life threatening clinical manifestations. The severity of the disease is independent from the type of mutation in the ABCC6 gene, and it has been suggested that local and/or systemic factors may contribute to the occurrence of clinical phenotype. The redox balance in the circulation of 27 PXE patients and of 50 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 40 publications
0
31
0
Order By: Relevance
“…Moreover, oxidative imbalance has been documented Perspective in serum from PXE patients [64] and in liver and serum samples of the Abcc6 knockout mouse [65]. If oxidative stress potentiates PXE-derived mineralization, dietary antioxidant supplements may be of particular therapeutic interest as a means of counteracting mineral deposition.…”
Section: Is Pxe Pathology Related To Oxidative Stress?mentioning
confidence: 99%
“…Moreover, oxidative imbalance has been documented Perspective in serum from PXE patients [64] and in liver and serum samples of the Abcc6 knockout mouse [65]. If oxidative stress potentiates PXE-derived mineralization, dietary antioxidant supplements may be of particular therapeutic interest as a means of counteracting mineral deposition.…”
Section: Is Pxe Pathology Related To Oxidative Stress?mentioning
confidence: 99%
“…However, these data may indicate that i) other factors, beside ABCC6 expression are involved in the pathogenesis of calcifications, ii) responsive fibroblasts or other mesenchymal cells are required in order to modify connective tissue homeostasis, and iii) independently from the primary gene defect, common pathways may be involved in these disorders. Within this context, it has been suggested that the elastic tissue injury in these patients may be the result of an oxidative process, induced by the combined and interactive effects of different factors (Aessopos et al, 1998;Garcia-Fernandez et al, 2008;Pasquali-Ronchetti et al, 2006). Plasma membrane microparticles, derived from the oxidative damage of red cell membranes by the effect of denatured hemoglobin products and free iron (Olivieri, 1999), as well as unbound fractions of hemoglobin and haem, which exceed the binding capacity of haptoglobin and hemopexin in the context of chronic hemolysis, have been considered to elicit inflammatory and oxidative reactions (Belcher et al, 2000;Gutteridge & Smith, 1988).…”
Section: Genetic Conditionsmentioning
confidence: 99%
“…Major advances concern diagnosis, due to ability to recognize a continuously increased number of mutations (mutation detection rate varies from 80-90%). Attempts to establish genotype/phenotype correlations have yielded little clinically useful information other than the fact that, as PXE patients age, symptoms get worse, probably because of progressive accumulation of mineralized elastic fibres, associated to other age-related degenerative features (Garcia-Fernandez et al, 2008). PXE is an important cause of blindness and of early death from cardiovascular manifestations (Neldner, 1988), therefore an early diagnosis is important in order to minimise the risk of systemic complications.…”
Section: Diagnosis and Treatmentsmentioning
confidence: 99%
See 2 more Smart Citations